La dimension cachée : introduction à des programmes de rééducation en milieu libre - Marineau, Daniel (Acta Criminologica)

(untitled) (Les Presses de l'Université de Montréal, 1974)
Abstract«THE HIDDEN DIMENSION : THE CIRCULAR INDEX» AN INTRODUCTION TO RE-EDUCATION PROGRAMS WITHIN THE COMMUNITYIt was in seeking to define and operationalize the prevention of juvenile delinquency that we discovered the circular index. First we will describe the method we followed in a clinical experiment and study on the marginal adolescent as he interacts with his school environment. Then we discuss our new understanding. Instead of seeing the social reality piecemeal, we saw it as a whole. There always seems to be a greater and greater distance between the evaluation in the form of detection, psycho-social and criminological evaluation and the supportive programs we are trying to elaborate and apply for reeducation within the community.The nosographic school is represented by the work of Hochman (1971). He asks whether this school has not reached its limits; he doubts its descriptive and prescriptive value. Nonetheless, we ask him to give us time, for to answer categorically in the affirmative can have grave consequences for a country or a province. While agreeing that our clinical and research theory belongs to a part of the nosographical school, it is not so much its descriptive and prescriptive value that is in question as the relationship between the two entities.This is why we are making a brief inventory of the outside restraints on our own clinical thinking. Among these, there is the lack of time available to the practitioner, his lack of resources, his inability to refer to the past, the difficulty of sharing his experience with that of others in a scientific manner, the mobility and uncertainty of the practitioner, etc.Second, we raise a number of restraints which are part of the clinical thinking of the practitioner. Two general types of restraints are described. The first refers to the different theoretical frames of reference of the practitioner, the second particularly concerns his work methods.Third, we place the linear index against the circular index. The linear index is defined as any evidence by which the first characteristic questions the individual's relations with abstract entities. The circular index is defined as any evidence attributed to an individual in relation to systems and groups. As to the systematizing of the circular index, we will have to wait another few months. Nevertheless, an example of the circular index is given through the study of a negative gang in the neighbourhood.The last part of the article deals with palliatives that can be used to reduce internal and external restraints on the clinical thinking and can but encourage this dialectic between the descriptive and prescriptive elements of the nosographic school. Among these palliatives, there is an urgent need to make an inventory of circular indices, to put them in order and to find the best methods to obtain them. In addition, a clinical table_mjist be constructed connecting the different resource items the practitioner needs to apply various supportive programs within the community once the accent is placed on rehabilitation, socialization and or the clinical prevention of the behaviour, and or the structure of the marginal personality.As a last palliative, we describe a way in which we give the client the evaluation we have made of him, explaining to him his behavioural and psychodynamic profile. For us, the aim of this last palliative is not only to evince greater respect for the client, but also to recognize his potential participation in his own program of treatment.